(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article examines the role of critical thinking in pedagogical psychology and its role in the formation of a high level of cognitive potential of the individual, the main psychological mechanisms serving the development of critical thinking in the modern educational process, questions and answers and discussion, problem-based learning, reflection, communication and cooperation, as well as the analysis of simulation and role-playing games, the development of metacognitive control, analytical thinking and independent decision-making skills in students, and the possibilities of integrating these mechanisms into the educational process.